Impact of Soft Powers on Income Inequality in South Asia: An Empirical Analysis (Journal of Asian Development Studies, 2020)
This study empirically investigates the impact of soft powers on income inequality in a penal of seven South Asian countries over the period from 1996 to 2016. The study incorporated population growth, dependency ratio, government effectiveness index, political stability index, net foreign assets, domestic credit, government expenditures, current account balance, expenditures on education, tax revenue, inflation, trade openness and real GDP growth as soft power measures to determine demography, governance, social, external, financial and economic power in single penal model. The study used Least Square Dummy Variable (LSDV) fixed effect model, random effect model and pooled OLS with standard model specification tests of Hausman and Breusch & Pagan Lagrangian Multiplier. The results of the study addressed that soft power measures are significantly effecting income inequality in South Asia. The results of the study are consistent with existing evidence on the subject the signs of the parameters are according to expectations. The study hold significant contribution in the literature as it fulfills the gap in existing literature by first time exploring wide ranged soft power determinants of income inequality in South Asia. The study with reference to previous evidence suggested that there is need of considering soft power factors in targeted policy reforms to determine income distribution of South Asian countries.